Perencanaan Strategis Sistem Informasi dengan Menggunakan Metode Ward and Peppard pada Swalayan - Jonathan Saputra; Andeka Rocky Tanaamah (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Abstract–Rapid technological developments require companies to move dynamically following the flow of technological changes, one of the things that can be done is to use information systems to support company operations. Harum Swalayan is one of the supermarkets that already uses information systems but there are still several divisions that have not implemented information systems. Data collection in this study used interviews and observations to determine the business environment and the company's information system environment. The method used in this study was Ward and Peppard with SWOT analysis, Value Chain analysis, Five Forces porter, and Mcfarlan's Strategic Grid. This research produces recommendations in the form of warehouse information system applications, vehicle parking security systems, and cashier information systems. Employee absenteeism system, and financial information system, which are priorities according to the McFarlan Strategic Grid mapping, and can be implemented within the next 3 years.